A CROSS-METAPHORICAL MAPPING VIDEO POSTER FOR ESL STUDENTS - Úbeda Mansilla, Paloma; Gómez-Ortiz, María (PEOPLE: International Journal of Social Sciences, 2018)
This paper describes a teaching and learning video poster tool designed for students of Architecture and students of Sports Science (ESL) as a second language at the Technical University of Madrid. These two major groups of students share a cross-metaphorical mapping that can be used as a cognitive approach to learn vocabulary in context using images and contexts closed to their field of studies. The metaphorical cross-mapping activity was the result obtained after publishing a bilingual dictionary handled under the research group of DISCYT from the Technical University of Madrid. The results obtained from them show a very fruitful and innovative material creation for (ESP) teaching in specific contexts. Additionally, the video poster provided additional written and oral task activities to work out in class.